Transportation in Green Logistics: A Bibliometric Analysis (2023)
The objective of this article is to offer a macroscopic vision on transport in green logistics through a bibliometric analysis. The information was gathered in Scopus with a sample of 604 documents from 2000 to 2022. The data was downloaded in March 26, 2023 and Microsoft Excel® and VOSviewer® were used to analyze the information. The central keyword was "green logistics" with the filters "transportation", "freight transportation", "freight transport", "transportation planning", "transportation system", "urban transportation" and "road transport". Among the most outstanding results, it was observed that the theme raised is recent, with a date of publication of no more than 25 years. In addition, of the 72 countries with publications, only 16 account for 89.9 % of the total, in which China stands out. Regarding the thematic areas, it was observed that the ones that are covered the most are engineering, computer science, and business. About the conclusions, it can be pointed out that technological advances in computing and clean energy are incorporated into the subject as they emerge. Also, it was observed that countries with high volumes of international trade are the most interested in making transport logistics more sustainable.  JEL Codes: Q50 Received: 25/05/2023.  Accepted: 17/08/2023.  Published: 10/10/2023.